Evaluasi Usability dan Penyusunan Rekomendasi Perbaikan Rancangan Antarmuka Pengguna pada Aplikasi Hi App - Bunga Octaviasari; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Hi App is a messenger application released in 2020 which was developed by a company in Indonesia called PT. Hello Indonesian Creations. The Hi App application has several features, namely to share messages, photos, videos, voices, documents, and language translation features. Hi App has been downloaded thousands of times. However, users feel that the Hi App application has shortcomings, including the use of English in the application, the layout design that does not use good color contrast, users who are confused about how to add friends' contacts, the Hi App font size cannot be made flexibly and the application also still has lag. The test used in this research is usability testing using task scenario and questionnaire. The test involved 5 respondents to work on task scenario assignments and fill out a questionnaire by 20 respondents. The evaluation results of the Hi App application include the user convenience aspect of 92%, the user speed aspect of 0.016, the user error aspect of 0.2, and the user satisfaction aspect of 20%-40%.